A Comprehensive Review of AI-Driven Strategies for Tailored Wellness and Dietary Recommendations - Nirav Pareshkumar Mehta (International Journal of Algorithms Design and Analysis Review, 2025)
In today’s fast-paced world, health and fitness have become top priorities for many individuals. As a result, people increasingly turn to mobile apps and digital tools to track their wellness goals, follow diet plans, and stay fit. However, most of these apps provide the same set of recommendations for all users, ignoring the fact that everyone has different needs. This one-size-fits-all approach often fails to keep users engaged and motivated, as it does not consider personal factors like age, medical conditions, fitness level, lifestyle habits, or cultural preferences. This study explores how artificial intelligence (AI) and machine learning can make these health apps more intelligent, responsive, and user-friendly by delivering personalized experiences. With the help of AI, apps can collect and analyze user data to create customized workout plans, meal suggestions, reminders, and wellness advice that are specifically tailored to each individual. These technologies can track changes over time and adjust recommendations based on progress, preferences, and feedback. In addition, personalization encourages users to take control of their health journeys by offering choices and flexible features that align with their goals and comfort levels. The study also examines the importance of data privacy and ethical use of personal information, ensuring that users feel safe and respected while using such apps. It highlights current challenges like algorithmic bias and data protection, and suggests solutions such as secure data handling practices, user consent, and compliance with regulations like GDPR and HIPAA. Drawing from a wide range of research and real-world examples, this review presents a complete picture of how AI-powered personalization can greatly enhance the impact of health and fitness applications. It shows that by putting users at the center and combining smart technology with ethical responsibility, we can create digital wellness tools that are not only more effective but also more inclusive, engaging, and sustainable in the long run.
Keywords: fitness level; health and fitness apps; health goals; motivation; one-size-fits-all; personalization; workouts